Pengaruh Pengetahuan dan Dukungan Keluarga Terhadap Pencapaian Asi Eksklusif di Kelurahan Hegersari Kota Banjar - Susilawati, Sri (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2024)
Breast milk is the first, primary, and best food for infants at the beginning of their lives. In the Hegarsari sub-district, which is part of the Pataruman I Community Health Center's working area, the rate of exclusive breastfeeding is still low. There are several factors that influence the achievement of exclusive breastfeeding, including mothers' knowledge about exclusive breastfeeding and family support. This study aims to determine the influence of knowledge and family support on exclusive breastfeeding rates in the Hegarsari subdistrict under the jurisdiction of the Pataruman I Health Center. This study uses quantitative testing, with research data collected from 51 respondents who are mothers with infants aged 0–6 months, using probability sampling techniques and simple random sampling. The analysis method used in this study was multiple linear regression analysis. The results of the study on the influence of knowledge and family support on exclusive breastfeeding achievement in Hegarsari Village, Banjar City, can be concluded that knowledge has an influence on exclusive breastfeeding achievement in Hegarsari Village, Banjar City, as indicated by a value of Sig, 0.000 and a sig value (0.000) < 0.05. Family support has an influence on exclusive breastfeeding achievement in Hegarsari Village, Banjar City, as indicated by the result of Sig,0.000 and the value of sig (0.000) < 0.05.